Patient Perspective on Diabetic Foot Care - Muhalla, Hafna Ilmy; Harianto, Susilo; Nursalam, Nursalam; Damayanti, Damayanti (International Journal of Psychosocial Rehabilitation, 2020)
A diabetic foot ulcer is the highest complication of diabetes mellitus, it increases the amputation rate. Ignorance and mistakes of foot care cause the increase the cases of diabetic foot, but foot care based on the patient perspective and what it means have never been explored in-depth. This study used a qualitative research with a phenomenology approach aimed to explore patient’s perspective about diabetic foot care at General Hospital in Gresik. Using an in-depth interview; fields note, recording; and memories note, the interview was conducted on 20 participants. Data collection was conducted by semi-structured interviews and analyzed by Braun and Clarke Thematic Analysis. The finding provides detailed information on eight main themes, that are foot care goals; urgency; area; type of care; the technique of care; education; diabetic foot prevention; and the last, consequences of an untreated foot. The conclusion is that patient’s perspective about foot care means caring for the foot; skin; nail; foot form, using warm water; appropriate footwear; lotion and identification of risk factors are the important ways to prevent ulcers and amputation. In fact, the health professional does not give complete information about foot care. Finally, diabetic foot care is an important way to prevent the appearance of diabetic foot ulcers, appropriate education and information from health professionals are needed to perfect perception about diabetic foot care.